KERUGIAN KONSTITUSIONAL TIDAK LANGSUNG DALAM PENGUJIAN UNDANG-UNDANG PEMILIHAN UMUM TERHADAP UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945: Indirect Constitutional Loss In The Testing Of Election Laws Against The Constitution Of The Republic Of Indonesia 1945 - Zahra Putri Ariana; Yogo Pamungkas (Faculty of Law, Universitas Trisakti, 2025)
Testing legislation against the Republic of Indonesia's 1945 Constitution is one of the Constitutional Court's several powers. Every law that is passed must comply with the Constitution and not be in contradiction with it, according to the Constitutional Court. The problem formulations in this article are how the Constitutional Court Panel of Judges' considerations of constitutional losses in the Constitutional Court Decision Number 90/PUU-XXI/2023 are reviewed from the General Election Law, as well as how the Petitioner's constitutional losses are reviewed from the General Election Law. The research method used is normative research, with primary and secondary data sources, and is qualitatively examined before drawing conclusions using deductive techniques. The results and conclusions are the Applicant's constitutional loss in Constitutional Court Decision Number 90/PUU-XXI/2023 was incorrect and did not adhere to Article 51 paragraph (1) of the Constitutional Court Law in conjunction with Article 4 paragraph (2) of PMK 2/2021, as well as that the Panel of Constitutional Justices' considerations of the constitutional loss in that same Constitutional Court Decision Number 90/PUU-XXI/2023 were incorrect and did not adhere to Article 51 paragraph (1) of the Constitutional Court Law in conjunction with Article 4 paragraph (2) of PMK 2/2021.